Novel aqueous nickel-bismuth batteries using NiMoO4@NiCo-layered double hydroxide heterostructure nanoarrays and Bi2O2CO3 microspheres as advanced electrode materials. (10th November 2019) - Kang, Weiwei; Sun, Ying; Xu, Bing; Li, Jie; Kong, Xiaodong; Huang, Dongfei; Zhang, Xueqin; Yang, Hong; Lin, Baoping
Abstract: Although considerable attentions have been paid to lithium ion batteries and supercapacitors, the trade-off between energy density, power density and cycling life is still need to be further improved. For achieving a win-win situation between these electrochemical performances, herein we introduce a novel strategy for constructing an advanced aqueous rechargeable nickel-bismuth battery, which was assembled for the first time with the NiMoO4 @NiCo-layered double hydroxide core/shell heterostructure nanoarrays directly grown on the nickel foam as the cathode and Bi2 O2 CO3 microspheres as the anode active materials. To obtain the new cathode with outstanding electrochemical performance, the growth condition of "core" materials (NiMoO4 nanoarray) and growth times of "shell" materials (NiCo-layered double hydroxide) coated onto the "core" materials were optimized systematically. The cathode exhibits a prominent specific capacity of 323.9 mA h/g at 1 A/g, good capacity retention of 67.8% in the current density range of 1–10 A/g and excellent conductivity along with fast electrolyte ions diffusion rates. As for the anode active materials, the Bi2 O2 CO3 microspheres display a high specific capacity of 186.3 mA h/g at 0.5 A/g, ultrahigh capacity retention of 90.1% in 0.5–10 A/g and excellent cycling stability. Desirably, the prepared nickel-bismuth battery can deliver a decent energy density of 46.7 W h/kg with the power density of 720 W/kg at 1 A/g, which are superior to that of the corresponding hybrid electrochemical capacitors with the same cathode yet commercial activated carbons as anode active materials. And the high power density of 5844.5 W/kg can also be obtained with the energy density of 22.6 W h/kg at 10 A/g. What's more, 53.2% of the initial capacity can be retained after 2000 cycles at 6 A/g. The excellent electrochemical performance can be put down to the elaborate architecture of electrodes and synergistic effect between active materials.